Aeroplane design study STOL airliner (A71). Part 3- low speed lift and control - Ward, R. E. (Cranfield Institute of Technology, 1972)
The potential application of advanced forms of aircraft control to civil operation appears to be capable of being split into two areas. First, those aircraft which are very large, whose rotary inertia tends to reduce the effectiveness of conventional controls. Second, those aircraft whose specification dictates that the aeroplane be flown at very low speed. Again conventional controls become inefficient due to decreased aerodynamic efficiency. The second category of aircraft has been considered in the form of an STOL aircraft. The control problems of an STOL aircraft with a 2000 ft runway capability (Ref.10) have been examined. It has been found that the aircraft is unstable and could require autostabilisation. None of the conventional controls were satisfactory and each required augmentation. The single strip crosswind requirement penalises the design most heavily since this requires over half of the extra control power necessary. The total augmentation for blowing air amounts to an equivalent thrust of approximately 6700 lb. This is equivalent to 11.5 per cent of the total installed aircraft thrust.